A Systematic Review of Cervical Ganglioneuromas. Issue 2 (June 2022) - Saadat, Saad; Fritz, Christian; Tran, Deanna; Parry, Nathan; Yuhan, Brian T.; Bolduan, Alyssa; Thorpe, Eric
Objective: To perform a systematic review of the literature evaluating clinical characteristics and management of cervical ganglioneuromas (CGNs). Data Sources: PubMed, Embase, and Cochrane Library databases were searched. Data such as patient demographics, imaging, and treatments were obtained. Review Methods: Pertinent studies were downloaded, and the full text was reviewed by 4 authors (N.P., S.S., C.F., D.T.). Results were reported via the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-analyses). Results: Fifty-two studies with 58 patients were identified in the literature. Of the 58 patients, 22 were adults and 36 were pediatric. The most common reported location of CGN was within the parapharyngeal space (76%), followed by the retropharyngeal (19%) and paravertebral/prevertebral (7%) spaces. The most common presenting symptoms included a nontender mass (29.3%), dysphagia (17.2%), and hoarseness (10.3%). Interestingly, the average tumor volume for patients with postoperative Horner's syndrome was 183 mm 3 (n = 21, 47.7%) vs 946 mm 3 in patients without Horner's syndrome (n = 23, 52.3%). This represents a statistically significant finding ( P = .018). There exists no significant difference in tumor volumes between adult and pediatric patients with Horner's syndrome ( P = .645). Conclusion: CGN is a rare tumor of the sympathetic nervous system. Management should involve complete surgical excision with biopsy. We found that patients with small-volume CGNs are significantly more likely to experience postoperative Horner's syndrome. This finding is independent of age and should therefore be taken into consideration in any patient with suspected CGN.